PHARMACEUTICO –ANALYTICAL STUDY ON ASHUDHA AND SHUDHA SHILAJATU - M.Pallavi; Gowda.Shankar; Doddamani. M.S (International Journal of Applied Ayurved Research, 2017)
Background: Shilajatu is considered one of the wonderful medicines of Ayurveda. Neither a plant nor animal substance, it is a mineral pitch that oozes from the rocks of Himalayas, as they become warm in the summer month. Shilajatu is a blackish brown exudation of variable consistancy found in the serene surroundings of Himalayas. Shilajatu has been given prime importance by the Acharyas. Materials and methods: Shodhana is a process by which impurities or poisonous materials of the substance are removed. The impure Shilajatu contains stony particles, sand, mud, wooden fibres and several metallic impurities leading to various diseases. So purification of Shilajatu is very essential. After purification it becomes brittle. Results: Total yield of SS was 40%. In the elemental analysis it showed the major presence of iron denoting the lohadrija shilajatu. Other analytical parameters like FTIR, XRD, HPTLC were done to both the samples. Conclusion: The sample taken for Shodhana was genuine in both ancient and modern parameters.